Pengaruh Profitabilitas (ROA) dan Leverage (DER) Terhadap Nilai Perusahaan (Tobin’s Q) dengan Corporate Social Responsibility (CSR) Sebagai Variabel Intervening - Achmad Agus Yasin Fadli (Disclosure, 2022)
The aims of this research is to examine (1) the inluence of profitability to the CSR (2) the inluence of leverage to the CSR (3) the inluence of profitability to the firm value (4) the inluence of leverage to the firm value (5) the inluence of CSR to the firm value (6) the inluence of profitabiluty to the firm value through CSR (7) the inluence of leverage to the firm value through CSR the manufacturing companies listed on the Indonesia Stock Exchange 2014-2018. The number of samples in the study were 18 compenies obtained using the purposive sampling method based on predetermined criteria. The data used is secondary data in the form of annual report in the periode 2014-2019 taken from the site www.idx.co.id. The data analysis technique used is descriptive statistic, classic assumption tests, multiple regression analysis tests and path analysis. The result of research showed that (1) profitability have a positive and significant impact on CSR (2) leverage have a positive and significant impact on CSR (3) profitability have a positive and significant impact on firm value (4) leverage have a positive and significant impact on firm value (5) CSR have a positive and significant impact on firm value (6) profitability have not effect on firm value through CSR (7) leverage have not effect on firm value through CSR